HOW DOES ISLAMIC BANKING SUPPORT ECONOMICS GROWTH? - Mustika Noor Mifrahi; Achmad Tohirin (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2020)
Some researchers have argued that the financial system has a vital role in economic growth. Islamic banking that has existed widely in many countries is expected to have a positive role in economic growth. This study aims to examine the impact of Islamic bank financing on economic growth in QISMUT countries. To compare with other full Islamic banking systems, Iran and Sudan also included in this study. By using annual panel data (2005-2015), this paper utilizes an approach to multiple mediating analysis models. The findings demonstrate that Islamic banking financing does not significantly impact economic growth directly. However, Islamic banking financing can possibly influence economic growth indirectly through investment and consumption spending.========================================================================================================Bagaimanakah Peran Perbankan Syariah dalam Pertumbuhan Ekonomi? Beberapa peneliti berpendapat bahwa system keuangan memiliki peran penting dalam pertumbuhan ekonomi. Perbankan Islam yang telah ada secara luas di banyak negara diduga memiliki peran positif dalam pertumbuhan ekonomi. Penelitian ini bertujuan untuk menguji peengaruh pembiayaan bank Islam pada pertumbuhan ekonomi di negara QISMUT. Iran dan Sudan dimasukkan dalam objek penelitian ini sebagai pembanding penggunaan sistem keuangan Islam. Menggunakan data panel tahun 2005-2015, penelitian ini menggunakan pendekatan analisis media dengan banyak faktor. Hasil penelitian menunjukkan bahwa pembiayaan bank Islam tidak dapat mempengaruhi pertumbuhan ekonomi secara langsung. Akan tetapi, Bank Islam dapat mempengaruhi pertumbuhan ekonomi secara tidak langsung, yaitu melaui investasi dan konsumsi.